Social Network Technology and its Implications for Libraries: Transforming the Library Services through the Web - Krishnamurthy, M.; Ashwath, Lalitha (Journal of Information and Knowledge, 2010)
The purpose of this paper is to understand how emerging social network technology services and transforming the structure of web and their potential, impact on library applications. This paper aims to explore the Library 2.0 a term that provides focus to a number of ongoing discussions centered on how libraries should make themselves and their services visible to end users and to one another. Social networking websites offer a social media platform free of charge for users to log on to their pc's and share exciting content. Informal social networking has existed since the inception web, but sites dedicated to social networking have been expanding exponentially since 2003. The concept of social networking must have been originated or evolved from the concept of sharing information. Current discussions on Social network development represent a significant development in the continuing interaction of technological developments and communications rights. Several issues in social networks are discussed. Libraries and librarians have increasingly been exploring social networking sites for both personal and professional resources.